New solution procedures for the order picker routing problem in U-shaped pick areas with a movable depot - Heiko Diefenbach; Simon Emde; Christoph H. Glock; Eric H. Grosse (OR Spectrum, 2021)
This paper develops new solution procedures for the order picker routing problem in U-shaped order picking zones with a movable depot, which has so far only been solved using simple heuristics. The paper presents the first exact solution approach, based on combinatorial Benders decomposition, as well as a heuristic approach based on dynamic programming that extends the idea of the venerable sweep algorithm. In a computational study, we demonstrate that the exact approach can solve small instances well, while the heuristic dynamic programming approach is fast and exhibits an average optimality gap close to zero in all test instances. Moreover, we investigate the influence of various storage assignment policies from the literature and compare them to a newly derived policy that is shown to be advantageous under certain circumstances. Secondly, we investigate the effects of having a movable depot compared to a fixed one and the influence of the effort to move the depot.
Keywords: 650; Order picking; Routing; Storage assignment; U-shaped pick area; Benders decomposition; Dynamic programming